Sustained effect of habitual feeding time on daily rhythm of core body temperature in mice - Ando, Hitoshi; Nagata, Naoto; Hosono, Takashi; Hasan, Nazmul; Morishige, Jun-ichi; Daikoku, Takiko; Maida, Yoshiko; Ono, Masanori; Fujiwara, Tomoko; Fujiwara, Hiroshi (Frontiers in Nutrition, 2022)
Background and Aim: Circadian clocks in most peripheral tissues are entrained mainly by feeding. Therefore, this study aimed to investigate whether the daily rhythm of core body temperature (CBT), including the effect of diet-induced thermogenesis, varies according to habitual feeding time. Methods: Wild-type and uncoupling protein 1 (UCP1) knockout mice were fed only during the first 4 h (Breakfast group) or the last 4 h of the dark period (Dinner group) for 17 days. On day 18, both groups were fed twice for 2 h, at the same starting times. Locomotor activity and CBT were measured continuously during the experiment. Results: On day 18, CBT increased at the beginning of each feeding period, regardless of the group and strain. However, the CBT increase induced by the first meal decreased sharply in the Breakfast group and mildly in the Dinner group; the opposite was observed after the second meal. In UCP1 knockout, but not wild-type, mice, the total amount of CBT was significantly lower in the Dinner group than in the Breakfast group. These effects were mostly independent of the locomotor activity and food intake. Conclusion: These results reveal that the effect of habitual feeding time on the daily rhythm of CBT is sustained at least until the following day. These effects may be mediated by both UCP1-dependent and -independent mechanisms.